2020
DOI: 10.1136/gutjnl-2020-321502
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of 2020 post-polypectomy surveillance guidelines in the Northern Ireland bowel cancer screening programme

Abstract: Contributors the report was devised and drafted by MBL. GI and HGC performed data analysis. WD and tAO contributed to data interpretation. All authors approved the final version. Funding HGC is funded by a Cancer research UK Career establishment Award (reference:C37703/ A25820). *These 609 high-risk cases under 2020 guidance (see ref. 1 for definitions) comprise: 371 cases with advanced polyp (AP) plus 1-3 other premalignant polyps (PMP) but total <5; 114 cases with ≥5 PMPs but no APs; 101 cases with ≥5 PMPs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
1
2
Order By: Relevance
“…The influence of changing criteria for stratifying risk has been previously shown in a recent study performed in the Northern Ireland Bowel Cancer Screening program evaluating the potential impact of the new British Society of Gastroenterology (BSG) 2020 guideline on surveillance regimens, compared to the previous 2010 guideline. The authors showed a 50.3 % reduction in the number of individuals scheduled for surveillance 19 , higher than that detected in the present study. However, in the Irish study, the reduction is essentially attributable to the disappearance of the “intermediate-risk” group in the new BSG 2020 guideline 4 , a group not existing neither in the ESGE 2013 nor in the USMSTF 2020 guidelines.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…The influence of changing criteria for stratifying risk has been previously shown in a recent study performed in the Northern Ireland Bowel Cancer Screening program evaluating the potential impact of the new British Society of Gastroenterology (BSG) 2020 guideline on surveillance regimens, compared to the previous 2010 guideline. The authors showed a 50.3 % reduction in the number of individuals scheduled for surveillance 19 , higher than that detected in the present study. However, in the Irish study, the reduction is essentially attributable to the disappearance of the “intermediate-risk” group in the new BSG 2020 guideline 4 , a group not existing neither in the ESGE 2013 nor in the USMSTF 2020 guidelines.…”
Section: Discussioncontrasting
confidence: 79%
“…regimens, compared to the previous 2010 guideline. The authors showed a 50.3% reduction in the number of individuals scheduled for surveillance [19], higher than that detected in the present study. However, in the Irish study, the reduction is essentially attributable to the disappearance of the "intermediaterisk" group in the new BSG 2020 guideline [4], a group not existing neither in the ESGE 2013 nor in the USMSTF 2020 guidelines.…”
Section: Accepted Manuscriptcontrasting
confidence: 79%
See 1 more Smart Citation